Enlightened investment in times of crisis - Kustin, B; Johnstone-Louis, M; Mayer, C (Conduit, 2020)
Conduit member Dr. Mary Johnstone-Louis, along with colleagues Dr. Bridget Kustin and Professor Colin Mayer CBE FBA, reflect on the role of family-owned companies when it comes to building a sustainable and just world post-COVID.